The Effect of Drug Abuse on Increased Criminality in the Community - Fajri, Agus; Risdalina, Risdalina; Kumalasari M, Indra (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research aims to find out and understand the correlation between narcotics abuse and the influence of increasing crime in the community. The type of research used is the type of legal research, Socio-legal research (legal research), or using the type of legal sociology study. The results of the discussion are: First, 1. Several factors that cause narcotics abuse include The desire to try narcotics because of curiosity, Lack of confidence, Using drugs as a lifestyle, Environmental influences, Work pressure, and a Disharmonious family (broken home); secondly, narcotics abuse has many negative effects on users, families, communities, nations, and states. Narcotics abuse is highly positively correlated with criminal acts, which often occur in almost all regions in Indonesia. The more the quantity of narcotics abuse increases, the more crime will occur. The criminal acts referred to include: Theft; Extortion; Spoliation; Pickpocketing; Robbery; Mugging; Rape; Sexual harassment, Obscenity; Murder; and so forth. So, it can be concluded that the abuse of narcotics and similar drugs can have a bad influence on users and other people and increase crime rates in society. The implications of this research emphasize the need for comprehensive policies and programs to prevent narcotics abuse and mitigate its impact on crime rates. This includes enhancing public awareness, improving family support systems, strengthening law enforcement, and providing effective rehabilitation programs to reduce the negative consequences on individuals and communities.